A 9-month retrospective evaluation of the aetiology and management of patients presenting with encephalitis/meningoencephalitis at a South London hospital. (5th February 2020) - Bharucha, Tehmina; Nashef, Lina; Moran, Nick; Watkins, Sue; Brown, David; Zuckerman, Mark
Abstract: Encephalitis causes high morbidity and mortality. An incidence of 4.3 cases of encephalitis/100 000 population has been reported in the UK. We performed a retrospective evaluation of the diagnosis and management of adults admitted to hospital with a clinical diagnosis of encephalitis/meningoencephalitis. Clinical, laboratory and radiological data were collated from electronic records. Thirty-six patients, median age 55 years and 24 (67%) male were included. The aetiology was confirmed over nine months in 25 (69%) of whom 16 were infections (six viral, seven bacterial, two parasitic and one viral and parasitic co-infection); 7 autoimmune; 1 metabolic and 1 neoplastic. Of 24 patients with fever, 15 (63%) had an infection. The median time to computed topography, magnetic resonance imaging and electroencephalography (EEG) was 1, 8 and 3 days respectively. Neuroimaging was abnormal in 25 (69%) and 17 (89%) had abnormal EEGs. Only 19 (53%) received aciclovir treatment. Six (17%) made good recoveries, 16 (44%) had moderate disability, 8 (22%) severe disability and 6 (17%) died. Outcomes were worse for those with an infectious cause. In summary, a diagnosis was made in 69.4% of patients admitted with encephalitis/meningoencephalitis. Autoimmune causes are important to consider at an early stage due to a successful response to treatment. Only 53% of patients received aciclovir on admission. Neuroimaging and EEG studies were delayed. The results of this work resulted in further developing the clinical algorithm for managing these patients.